FIRE CLASS WEBSITE: A DIGITAL TRAINING PLATFORM TO ENHANCE ARFF EMERGENCY PREPAREDNESS AT AIRPORT - Hamim Syahadat (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2025)
Emergency Response Planning (ERP) is a comprehensive framework developed and periodically evaluated by airport operators to address potential threats that may affect aviation safety and operational continuity. However, conventional training methods still limit personnel’s access to updated learning resources. This study aims to develop the Fire Class website as a digital learning platform that provides structured ERP training materials to improve the training effectiveness of Airport Rescue and Firefighting (ARFF) personnel. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Quantitative data were analyzed through expert validation and user assessments. The results show that the Fire Class website achieved a “Highly Feasible” category with an expert evaluation score of 93.3% and a user satisfaction score of 90.8%, indicating strong acceptance and usability. These findings confirm that web-based learning media are effective in enhancing training accessibility, flexibility, and engagement for ARFF personnel. The Fire Class website contributes to the digital transformation of aviation safety education by providing an adaptive, cost-efficient, and scalable model for continuous professional development.